The Impact Of Branchless Banking On Banking Profitability In Indonesia: Difference In Difference Approach (The Indonesian Journal of Business Administration, 2022)
Abstract. In increasing financial inclusion in Indonesia, the Financial Services Authority (OJK), in collaboration with Bank Indonesia (BI), implemented the Financial Services Authority Regulation (POJK) No.19/POJK.03/2014 program, namely Digital Financial Services (LKD) and Laku Pandai, otherwise known as branchless banking. Branchless banking is very useful for people who have never been touched by banking. Branchless banking is very useful for people who have never been touched by banking. This service is provided without an office network, but with cooperation with other parties and support from the use of information technology facilities. This study aims to determine the impact of branchless banking on the level of profitability in banks that have implemented branchless banking services. This study used 7 banks as the treatment group and 14 banks as the control group, from 2005-2020. The method used is difference in difference (DiD) which will compare before and after the implementation of branchless banking by eliminating other factors that can bias the results. The results showed that branchless banking has a positive impact on the level of profitability. The level of profitability as measured by ROA, ROE and NIM has increased significantly and BOPO has decreased. So, it can be concluded that there are differences in the level of profitability before and after the implementation of branchless banking.Keywords: DiD, Conventional Banking, Branchless banking, Profitability.